Tualang honey in head and neck cancer patients: effects on cancer related fatigue and quality of life - Ramasamy, Viji (2018)
Introduction:Cancer related fatigue (CRF) is a problem experienced by head and neck cancer patients, especially those who underwent chemoradiation therapy.CRF may persist for years post chemoradiation therapy and significantly impair their quality of life (QOL).Tualang honey is rich in amino acids, vitamins, minerals and enzymes. It is proven to have anti-inflammatory, antioxidant and anti-tumour properties. As CRF is related to inflammatory mediators, the effects of Tualang Honey may improve CRF.The aim of this study is to determine if Tualang honey has a role in improving CRF and quality of life among head and neck cancer patients post chemoradiation. Methodology: In this open labelled randomized clinical trial, 40 participants aged between 18 and 65 with head and neck cancer who completed radiotherapy and/or chemotherapy in Hospital USM, Kelantan Malaysia or Hospital Taiping were recruited and randomized into two groups; experimental group (Tualang honey) or control group (Vitamin C). They were prescribed with either daily oral Tualang honey 20mg or tablet vitamin C 100 mg for 8 weeks.Level of fatigue and quality of life were measured usingFACIT-Fatigue and FACT H&N questionnaires at baseline, 4 weeks and 8 weeks. The white cell countand C-reactive protein level were measured at baseline, 4 weeks and 8 weeks. Results: After four and eight weeks of treatment with Tualang honey or Vitamin C, the fatigue level for study group was better than in the control group, and the differences were statistically significant (p<0.05). Statistically significant improvements were seen on quality of life (p<0.05) for the study group at week 8, however, no significant improvements were seen in white cell count and C-reactive protein level between control and study group. Conclusion: Our study provided support for the use of Tualang honey to improve CRF and QOL. The positive results of this study warrant further studies in this field.